The effectiveness of using paid advertisements on Instagram to increase sales at Grooveart Music Course - Aileen Christabella Setiana (Review of Management, Accounting, and Business Studies, 2021)
In the development of marketing strategies, the use of social media marketing is increasing every day, but not all companies are able to maximize social media for their company's promotional activities. The less-than-optimal use of social media for promotional tools can decrease a company’. This research was conducted with the aim of knowing how effective the use of paid Instagram ads as a social media marketing tool is in attracting customers’ intention to use the services of Grooveart Music Course and the advantages of using paid Instagram ads for Grooveart Music Course. This study used a qualitative approach, where data were obtained by conducting interviews and passive observation of five informants from the Grooveart Music Course. The results of this study showed that using paid advertising on Instagram is considered an effective thing to do, as evidenced by the large number of new students who enroll in Grooveart Music Course. Grooveart Music Course also achieved various advantages, after using paid Instagram ads.